Limb Body Wall Complex: First Trimester Ultrasonographic Diagnosis of a Case with Exencephaly and Megacystis - Mert Turğal; Aslıhan Yazıcıoğlu; Özgür Özyüncü; M. Sinan Beksaç (Medical Network, 2016)
Limb Body Wall Complex (LBWC) is a rare developmental anomaly which is classified together with midline defects. Despite the anomaly arises from an error occuring during the embryonic folding, the exact pathophysiological mechanisms are poorly understood. The clinical picture is characterized by thoracoabdominoschisis, eventration of the internal organs, limb reduction defects and sometimes craniofacial abnormalities. In this report we present (with the informed consent of the patient) the first trimester ultrasonographic diagnosis of a fetus with the classical findings of LBWC accompanied by exencephaly, megacystis and kyphoscoliosis which are rare in the literature. Today, this mortal anomaly can be diagnosed during the early weeks of gestation by ultrasonography. Prenatal detection of the anomaly is critical since offers an option of pregnancy termination.